Analisis Tarif Jalan Tol Berdasarkan Pendekatan Ability To Pay (ATP) dan Willingness To Pay (WTP) (Studi Kasus: Jalan Tol Bakauheni-Terbanggi Besar) - Winarsih, Anita Lestari Condro; Muthaher, Andi Muflih Marsuq (Jurnal Proyek Teknik Sipil, 2025)
Bakauheni-Terbanggi Besar Toll Road is the main transportation route connecting to South Lampung, Bandar Lampung, Pesawaran, and Central Lampung. Although the location of the Bakauheni-Terbanggi Besar Toll Road is quite strategic, based on the business plan document and the recapitulation of the Bakauheni-Terbanggi Besar Toll Road LHR has a 2021 LHR plan of 20,295 vehicles / day, while the realization LHR is only 11,674 vehicles / day. The traffic situation on the toll road that is not as planned is suspected to be caused by a mismatch of tariffs with the ability and willingness to pay the community, and the current tariff is ±850 / km (category 1 vehicles). Therefore, it is necessary to analyze the adjustment of toll rates with the financial condition of toll road users. In this study, the method used is the calculation of Ability to Pay (ATP) and Willingness to Pay (WTP). The data collection was carried out by distributing questionnaires to 150 respondents. Based on the results of the analysis, the ATP rate of Rp 628 / Km and the WTP rate of Rp 600 / Km. Based on the ATP and WTP relationship graph, the ideal rate for group one vehicles is Rp 626,28 / Km with the percentage of respondents who can afford and are willing to pay at 85,1%.